Emerging Cross-Curricular Diversification and Implementation in Educational Institutions for Sustainable Development: Teacher Educators’ Perspectives in Ogun State of Nigeria - Alade , Ibiwumi A.; A. Ojo , Adebowale (African Journal of Education,Science and Technology (AJEST), 2018)
The phrase sustainable development as a concept is one of the emerging international environmental rhetorics the world over which has become a curricular issue for all and sundry. It gained prominence in 1992 at the United Nations (UN) Conference held in Rio de Janeiro where it was agreed that Sustainable Development (SD) can be achieved essentially through the process of education. As a result, since the beginning of the 21st century in Nigeria, sustainable development issue is being addressed through curriculum innovations and curriculum offerings. This study examined cross-curricular diversification and implementation in Nigerian educational institutions for sustainable development. In the descriptive survey, three research questions were raised, and Cross-curricular Offerings for Sustainable Development Scale (COSDS) with a reliability index of 0.81 was used for data collection. A total of 400 teacher educators were randomly sampled from educational institutions in Ogun State, Nigeria. The study revealed that the participants’ level of awareness of innovative curricula in Nigerian education for sustainable development was highest for civic education / citizenship education (100.0%) and lowest for capital market studies (20.0%). The challenges affecting cross-curricular diversification and implementation include curriculum overload (62.50), lack of adequate interdepartmental collaboration (73.8%) and structural curricular problem (66.0%). The researchers recommended the need for further promotion of curricular diversification by giving more attention to the strategies submitted in this study.